Mini Literature Review of Self-Concept - Aida Mehrad (Journal of Educational, Health and Community Psychology, 2016)
AbstractThe aim of the current  literature review is to focus on individuals´ self-concept. The results of the present study reveal that self-concept assumed as an important factor for each and can change his or her belief, attitude, and reaction toward personal and social life. This study likewise  explained the beginning of self-concept, different views toward this vital factor, the role of introspection, and multicultural. Furthermore, this paper supported the imperative of self-concept; additionally, it has an essential  role in individual advance. Keyword: self-concept, individual, attitude,